Linguagem e identidade em contextos institucionais - Magalhães, Izabel (Cadernos de Linguagem e Sociedade, 2010)
People’s identities are currently seen as a focus of interest in a number of language studies which have adopted a criticai perspective. The purpose of the present study is to discuss how the identities of adult literacy learners are constituted in text. The study explores intertextuality following work by Mikhail Bakhtin (1986) and Norman Fairclough (1992a). The main finding points to heterogeneity in the subject of educational discourse. Two categories of subject are defined: the disciplinary subject and the community subject. These categories often oppose each other but can at times coexist. In learners’ texts, a community voice can be heard in its particular language which seems to resist schooled literacy practice. Such language is characterised by textual transformation.